Disseminated Intravascular Coagulopathy Caused by Uterine Leiomyoma with Sarcoma-Like Findings on Magnetic Resonance Imaging - Akiyo Taneichi; Hiroyuki Fujiwara; Yukako Mizoguchi; Shizuo Machida; Hiroaki Nonaka; Yuji Takei; Yasushi Saga; Mitsuaki Suzuki (Hindawi Limited, 2014)
A leiomyoma rarely causes disseminated intravascular coagulopathy (DIC). In the present report, we describe a case of DIC caused by leiomyoma. A 36-year-old nulliparous woman presented with hypermenorrhea and a lower abdominal mass. On magnetic resonance imaging, we detected a 14 cm uterine tumor, which was suspected to be a sarcoma. Blood tests at the preoperative examination indicated platelet count of 9.6 × 104/μL, fibrin degradation product level of 107.1 μg/mL (normal value, 0-5.0 μg/mL), and fibrinogen level of 54 mg/dL (normal value, 129-271 mg/dL). Based on these findings, we diagnosed the patient with DIC. The patient was treated with nafamostat mesilate and fresh frozen plasma, but the DIC did not show any improvement. Subsequently, a hysterectomy was performed, after which the DIC improved. Clinicopathological findings indicated the presence of a leiomyoma with multiple vessels containing thromboemboli, and suggested that the DIC was caused by the leiomyoma. Therefore, it is essential to consider that that a benign leiomyoma may be a cause of DIC.